Appunti sulla Parigi di Walter Benjamin: superamento nel moderno e non del moderno? - Distaso, Leonardo V. (Bollettino Filosofico, 2016)
In a speech of 1864 Haussmann has showed his hate for Parisians: they are devoid of roots. The metropolis uproots and bewilders and it's so difficult for the voluntary memory recovering the ancient and eternal sense of the value. Art shelters in the password of the art pour l'art and so it loses its role and contact with society. So that the flâneur can do the historical awakening by the recovering of unvoluntary memory of the correspondances that vivify the metropolis and his historical nature. The surrealism is the chance of this awakening.